Is the long-term mortality similar in COVID-19 and community-acquired pneumonia? - Méndez, Raúl; González-Jiménez, Paula; Latorre, Ana; Mengot, Noé; Zalacain, Rafael; Ruiz, Luis A.; Serrano, Leyre; España, Pedro P.; Uranga, Ane; Cillóniz, Catia; Hervás, David; Torres, Antoni; et al. (Frontiers in Medicine, 2023)
Introduction There are no data on the association of type of pneumonia and long-term mortality by the type of pneumonia (COVID-19 or community-acquired pneumonia [CAP]) on long-term mortality after an adjustment for potential confounding variables. We aimed to assess the type of pneumonia and risk factors for long-term mortality in patients who were hospitalized in conventional ward and later discharged. Methods Retrospective analysis of two prospective and multicentre cohorts of hospitalized patients with COVID-19 and CAP. The main outcome under study was 1-year mortality in hospitalized patients in conventional ward and later discharged. We adjusted a Bayesian logistic regression model to assess associations between the type of pneumonia and 1-year mortality controlling for confounders. Results The study included a total of 1,693 and 2,374 discharged patients in the COVID-19 and CAP cohorts, respectively. Of these, 1,525 (90.1%) and 2,249 (95%) patients underwent analysis. Until 1-year follow-up, 69 (4.5%) and 148 (6.6%) patients from the COVID-19 and CAP cohorts, respectively, died (p = 0.008). However, the Bayesian model showed a low probability of effect (PE) of finding relevant differences in long-term mortality between CAP and COVID-19 (odds ratio 1.127, 95% credibility interval 0.862–1.591; PE = 0.774). Conclusion COVID-19 and CAP have similar long-term mortality after adjusting for potential confounders.